Igneous Rock Associations 24. Near-Earth Asteroid Resources: A Review - Innis, Liam Robert John; Osinski, Gordon R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2019)
The extraction of natural resources located beyond Earth to create products can be described as space resource utilization (SRU). SRU is under active investigation in both the public and private sectors. Near-Earth asteroids (NEAs) are particularly promising early SRU targets due to their relative proximity and enrichments in two key resources: water and platinum group elements (PGEs). Water can be used to create rocket propellant, making it the only resource with significant demand given the current nascent state of the space market. Platinum group elements are valuable enough that their import to the Earth market is potentially economical, making them the other prospective resource in the current embryonic state of SRU. While it is possible to retrieve material from a NEA, doing so on an economical scale will require significant developments in areas such as autonomous robotics and propulsion technology. A parameterization accounting for asteroid size, resource concentration, and accessibility yields just seven and three potentially viable NEA targets in the known population for water and PGEs, respectively. A greater emphasis on spectral observation of asteroids is required to better inform target selection for early prospecting spacecraft. A further complication is the lack of a legal precedent for the sale of extraterrestrial resources. The Outer Space Treaty prohibits the appropriation of celestial bodies but makes no explicit reference to their resources while the U.S.A. and Luxembourg have passed legislation entitling their citizens to own and sell space resources. Whether these laws are a matter of clarification or contradiction is the matter of some debate.